Urban flood risk mitigation : A perspective form urban planning - Brandow, Andreas (Luleå tekniska universitet, Institutionen för samhällsbyggnad och naturresurser, 2023)
Due to the global warming and climate change, an increased frequency of high intensity rains and other disasters are expected all around the world. To predict this change in climate the IPCC has created a set of climate scenarios, RCPs, that will try to predict the future climate based on how much we are able to adapt and mitigate the effects we as a species have on the environment. This master thesis will seek to explore the possibility to use urban planning tools to help mitigate the increased effects and sizes of floods due to the global warming. To achieve this, a case study of Luleå is done, where urban indicators are used to improve the resilience of the city. This is combined with a policy study to see how Luleå compare to other cities in their policies that affect flood protection and mitigation. To have a strong flood protection system in a city several factors need to be considered. One of the biggest factors is what type of strategy is chosen. One possible strategy is resilience, this combines seeming paradoxes into a working flood protection and mitigation plan. Resilience improves the flood protection and mitigation by combining and improving the robustness, adaptability, and transformability of the city. This is done by, among other things promoting inter disciplinary cooperation, public cooperation and knowledge of flooding, and promoting the use of water in the city as an asset. Blue and green infrastructure could also be implemented into the city as these measures help improve the resilience of a city in many regards. Not just for flood protection, but it can also help mitigate the effects of droughts or heatwaves and improve the general wellbeing of the citizens. In the policy study it was found that different cities varied in both scale and strategy in their flood protection measures. All the cities that were looked at would also need to increase the scale of their protection and mitigation measures to mitigate the increased size and frequencies that the climate change brings. In Sweden, ...